DIPG-58. Therapeutic HDAC targeting in hypermutant CNS tumors. (3rd June 2022) - Myers, Carrie; Noll, Alyssa; Biery, Matthew; Meechan, Michael; Tahiri, Sophie; Foster, Jessica; Dun, Matthew; Olson, James; Vitanza, Nicholas
Abstract: Diffuse intrinsic pontine glioma (DIPG) is a universally fatal tumor of the pons, most often characterized by mutations in genes encoding histone 3, that led to the classification diffuse midline glioma, H3 K27M-mutant (DMG). However, 15% of DIPG are histone wildtype (H3WT) and can have a hypermutant phenotype, characterized by mutations in DNA mismatch repair that also occur in pediatric high-grade glioma (pHGG). We previously published the preclinical efficacy of quisinostat in DMG. As hypermutant CNS tumors share transcriptional disruption with DMG, we investigated if HDAC inhibition was also therapeutic against hypermutant DIPG and pHGG. We tested PBT-24, a PMS2 mutant, treatment-naïve, patient-derived hypermutant DIPG model, and found similar quisinostat sensitivity compared to other DMG cultures in vitro (IC50 = 30 nM), as well as significant efficacy in a xenograft flank model (60 day mean tumor size of 1109mm3 [vehicle] vs. 19mm3 [quisinostat-treated]). This in vivo effect was greater than the anti-tumor effect observed in a xenograft flank non-hypermutant DMG model PBT-09 (60 day mean tumor size of 1006mm3 [vehicle] vs. 244mm3 [quisinostat-treated]). To validate the effect of hypermutation on sensitivity to quisinostat, we generated PMS2 knock-out (KO) and MSH2 KO isogenic cell lines using the H3WT model VUMC-DIPG-10. In a xenograft flank model, we observed increased quisinostat sensitivity in the KO models (20 day mean tumor volume of 547mm3 [parental], 396mm3 [PMS2 KO], and 150mm3 [MSH2 KO]). RNA sequencing of quisinostat-treated PBT-24 revealed an increase in acute inflammatory response genes which we are investigating as a mechanism of action for HDACi against hypermutant tumors. Ultimately, we demonstrate the in vivo efficacy of quisinostat against hypermutant DIPG that supports the investigation of HDAC inhibition as a treatment strategy across hypermutant CNS tumors.